Study protocol: Apps and peer support for a healthy future and living well with diabetes (APHLID-M) - K.O. Mathews; F. MacMillan; V. Wong; M. Craig; J.R. Greenfield; R. Hicks; T. Jones; A. Poynten; T. Wong; M. Reyes; K. Tannous; C. Wilson; et al. (Contemporary Clinical Trials Communications)
1 Abstract: Background: Mental health conditions are common among non-pregnant young people with any form of diabetes, affecting diabetes self-management and increasing complications risk. Limited evidence exists on whether smartphone applications “apps” combining diabetes and mental health (MH) support can improve self-management and MH in these young people. The Apps and Peer support for a Healthy future and Living Well with Diabetes (APHLID-M) multicentre study includes two randomised controlled trials (RCTs) testing such an app, aimed at reducing distress among young adults with diabetes with and without a mental health condition (MHC). Methods and analysis: An app containing diabetes and MH resources was configured onto a pre-existing, digital health platform. Young adults aged 16–30 years with diabetes will be recruited from eight Australian outpatient clinics, screened using the Kessler Psychological Distress Scale (K10) and the Problem Areas in Diabetes (PAID) questionnaires. Based on MH status, participants will be allocated to the primary RCT (MHC group) or a nested-exploratory RCT (No-MHC group) and randomised by site to the “app” (Intervention) or “no app” (control). All participants will have access to peer support and will continue to receive standard diabetes care through their clinic. Recruitment will end once 142 participants are enrolled in the primary RCT. The primary outcome is change in psychological distress (K10), and the secondary outcome change in HbA1c, assessed at baseline and 6 months. Discussion: APHLID-M will offer valuable insights into effects of digital technology in enhancing MH (particularly distress) physical health and well-being in young people with diabetes.